PENGARUH MEDIA BUKU DIGITAL ECOSTORY TERHADAP PENGETAHUAN LINGKUNGAN ALAM ANAK USIA 5-6 TAHUN - Alfiyah Haniah Fitriani; Nur Rochimah; Ine Nirmala (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Environmental knowledge among early childhood learners is a foundation for building lifelong environmental awareness, yet children aged 5-6 years at TK Islam Annajah, East Jakarta, showed limited understanding of natural environmental elements, the distinction between biotic and abiotic components, and responsible behaviour toward nature. This study aimed to examine the level of children's environmental knowledge before and after the use of the Ecostory digital storybook and to determine whether the media produced a significant difference. A quantitative approach with a one-group pretest-posttest pre-experimental design was employed. The sample consisted of 24 children in Group B, selected through saturation sampling. Data were collected using an observation instrument of 29 valid and reliable items (Cronbach's Alpha = 0.964) covering knowledge of living things, natural components, and human-environment relationships, administered before and after eight treatment sessions using the Ecostory digital storybook. Data were analysed using the Shapiro-Wilk normality test, Levene's homogeneity test, and a paired-samples t-test. The mean pretest score was 46.125 (SD = 4.236), which increased to 66.250 (SD = 4.296) at posttest, with an average N-Gain of 0.286 (29%, low category). The paired-samples t-test showed t = -17.374, df = 23, and Sig. (2-tailed) = 0.000 (< 0.05), so H0 was rejected. It is concluded that the Ecostory digital storybook media has a positive and significant effect on the environmental knowledge of children aged 5-6 years.